KINETIKA ADSORPSI Cr(VI) MENGGUNAKAN ADSORBEN MAGNETIT (Fe 3 O 4 ) DAN MAGNETIT TERLAPIS ASAM HUMAT (Fe 3 O 4 /AH) - Soerja Koesnarpadi; Daniel Tarigan (PROSIDING SEMINAR KIMIA, 2014)
The adsorption kinetics of Cr(VI) by two adsorbents, i.e. magnetite (Fe 3 O 4 ) and magnetite coated humic acids (Fe 3 O 4 /HA) have been studied. Adsorbent of Fe 3 O 4 and Fe 3 O 4 /HA were synthesized by co-precipitation method and then characterized by FT-IR, XRD and TEM image measurements. The acidity of the solution was adjusted to pH 3, comparasion on the adsorption kinetics of Cr(VI) on Fe 3 O 4 between Fe 3 O 4 /HA. The FT-IR spectra revealed the presence of main fuctional groups of Fe-O and C-O at free carboxylate acid in Fe 3 O 4 /HA and those of only Fe-O in Fe 3 O 4 . The two adsorbent had similar diffraction peaks at 2θ. The TEM image demonstaretd that Fe 3 O 4 were spherical in shape and uniform distribution and then Fe 3 O 4 /HA had no uniform size. Adsorption of Cr(VI) by Fe 3 O 4 was much faster than Fe 3 O 4 /HA at the acidity of pH 3, with adsorption rate constant (k) of 0.013 g.mg -1 .menit -1 for Fe 3 O 4 and 0.0062 g.mg -1 .menit -1 for Fe 3 O 4 /HA. The two adsorbents were giving a model of adsorption kinetics Ho (pseudo order 2).